Faktor yang Mempengaruhi Kepemimpinan dalam Pendidikan Islam - Safitri, Amalia Nur Ajeng; Wicun, Dina; Widyastuti, Iis; Ma’shum, Muhammad Azhar (Lembaga Yasin AlSys, 2022)
Education is a form of organization Here, success is largely determined by management and leadership factors. How big is this fact of leadership in education? Therefore, it is very important to improve the education management system and governance. Technology development is in line with social changes in society, and leadership also faces challenges that are consistent with those of technology development. This study is a literature review that looks at various references to find problems from that study. From the survey results conducted, the survey results are as follows. First, from a sociological point of view, leadership is leadership that faces challenges as technology advances. To address this, as a leader, you need to implement an fair system that maintains the core values ​​of Islam. Second, from a political point of view, leadership faces individuals, institutions, organizations, political parties, and leaders who face challenges with other institutions that meet those challenges at their request. is. Get ready and compete in a healthy way. Support from external or politically expected funding.